STUDI GASTRONOMI: REVITALISASI GABUS PUCUNG SEBAGAI SARANA PEMBELAJARAN MENGENAL WARISAN KULINER BETAWI DI SEKOLAH DASAR - Afifah, Aulya Nur; Viori, Ravinska Vigna; Aryanto, Sani (Journal of Professional Elementary Education, 2025)
Gastronomy is a form of communication to convey the culture, history and identity of a society through food/culinary. In Elementary school, learning about gastronomy can be done through recognizing traditional foods, so that students can understand the diversity of Indonesia Culture. This research aims to find out about cork pucung culinary as a means of learning gastronomy and Betawi cultural identity. The method used is Literature Review. The results of this study show that gastronomy is not only related to culinary as the main aspect, but also reflects the history, culture, geographical landscape, and cooking methods that form the identity of a society. Gabus pucung, as one of the Betawi culinary heritages, has strong historical and cultural values, but is experiencing challenges in terms of its preservation due to changes in the consumption patterns of modern society. Gabus pucung, as a typical Betawi dish, reflects local wisdom in food utilisation and has a deep historical value. Preservation efforts through education, promotion, and innovation in presentation and marketing can be an effective strategy in maintaining the existence of this culinary in the midst of changes in people's consumption patterns.